Genotype×Environment Interaction and Stability Analysis for Quality Parameters in Little Millet (Panicum sumatrense L.) - Dela, G. J.; Patil, Harshal E.; Vadodariya, G. D.; Patel, U. N.; Ray, Purnima (International Journal of Economic Plants, 2023)
The present study was conducted to evaluate Genotype×Environment interaction and stability analysis for quality parameters for 9 observations in 50 little millet genotypes under three environments i.e.Waghai, Vanarasi and Navsari locations under Gujarat, India during the year kharif-2020. Stability analysis revealed that G×E interaction was significantly differed for all the characters except calcium content (mg 100 g-1) and ash content (mg 100 g-1) indicated that different genotypes reacted differently to different environmental conditions. Estimates of environmental indices indicated that Waghai location was favourable for yield contributing characters along with quality parameters followed by Navsari and Vanarasi. The results of present study revealed that none of the genotypes exhibited average stability for all the characters. Among the genotypes, WV 262, WV 258, WV 256, WV 293 and WV 273 were found average stable over environments for grain yield plant-1 with quality parameters. So, these genotypes may be used in further breeding programme in little millet.